S. Carrera, J. Santos Vara y T. Strik (eds.): Constitutionalising the external dimensions of EU migration policies in times of crisis. Legality, rule of law and fundamental rights reconsidered, Edward Elgar Publishing, 2019, 323 págs. - Porras Ramírez, José María (Revista de Derecho Comunitario Europeo, 2020)
Sin resumen